KONSEPTUALISASI PENERAPAN PERADILAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PEDOFILIA DI INDONESIA - Rama Setyo Prakoso; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Pedophilia occurs in various places, in several acts and various types ofperpetrators. Resolutions of this problem have not stop in one form. Using theconcept of Restorative Justice to achieve humanitarian justice is a concept thatwill be a progressive step in the settlement of non-criminal pedophilia. Thisresearch aims to: first, understand the current regulations for pedophiles inIndonesia, second, to find out the relevance of Restorative Justice to be applied inthe criminal prosecution of pedophilia in Indonesia.This type of research is classified as a normative study using concept ofRestorative Justice and correlation principle to approach the issues, secondarydata is used by collecting data from library research, analyzed by qualitativejuridical analysis and concluded using descriptive analytical methods.From this research we can conclude two main things. First, the currentregulations for pedophiles in Indonesia can now be found in the Criminal Code(KUHP) and Law Number 23 Year 2002 concerning Child Protection, which ischanged into Law Number 35 Year 2014 junto Act Number 23 of 2002 concerningChild Protection, which then underwent a second change with Act Number 17 of2016 concerning the Establishment of Perpu Number 1 of 2016 into Law.However, in this regulation, the punishment only focus on the detention of theperpetrators without considering other factors behind their actions, and did notprovide definitive protection for victims. Second, the relevance of restorativejustice (Restorative Justice) to be applied in Indonesia to pedophilia criminalcases in terms of several aspects such as; ethics and values of the Pancasila andIndonesia’s culture are not conflicted and can be coincide. So, the concept ofrestorative justice against pedophile perpetrators can be applied in Indonesiawith the right and appropriate arrangements.Keywords: Pedophilia, Restorative Justice, Children